Updated fluid recommendation: position statement from the international marathon medical directors association (IMMDA) - Hew-Butler, T.; Verbalis, J. G.; Noakes, T. D. (Clinical Journal of Sport Medicine, 2006)
This article will focus on the physiology of normal fluid balance as the ultimate guide toward the evolution of optimal fluid recommendations. Six physiologic considerations of fluid and sodium balance will be detailed followed by 6 practical recommendations. The neuroendocrine regulation of homeostasis will be emphasized in defense of the behavioral drives for thirst and sodium palatability during dynamic activities such as prolonged endurance exercise. The behavioral drives to maintain fluid and sodium balance are evolutionary stable, essential for the safety and survival of the species, and deeply rooted within the human genetic makeup.